Creep behaviour of cracked steel and macro-synthetic fibre reinforced concrete - Zerbino, Raúl Luis (2015)
The study of creep behaviour of fibre concrete in cracked conditions is nowadays one of the main subjects of interest; many research groups in the world are working on this matter and the development of test methods and the definition of parameters for its characterization becomes an urgent necessity. This paper explores the use of different types and levels of long term bending loads and compares the creep rates of fibre reinforced concretes (FRC) incorporating steel and two macro-synthetic fibres. Tests arrangements with three and four point loadings were used. An initial crack width of 0.5 mm was adopted. It was verified that the creep rate clearly increases in macro-synthetic FRC and that the application of loading–unloading cycles does not imply significant changes in the creep rate when compared to permanent loads of similar magnitude. After creep tests the remaining residual bending capacity of FRC is considerable. Similar creep behaviour was observed by using three or four point loading configuration.